Improved Learning Management Process Writing Through Daily Journals for Authentic Assessment in Junior High School - Haerul Haerul (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
One of the problems found in schools is the low level of student's writing skills, especially paragraph writing skills. This happens because the writing learning strategy has not provided students with more opportunities to express ideas in writing more freely, expressively, and spontaneously. Learning to write has not encouraged the formation of writing habits in students. On the other hand, the applied writing learning assessment has not provided actual information about the development of students' writing skills. To overcome this, journal writing activities were applied to students and utilized the writings in the journal for authentic assessment materials. In its application, the journal writing activity is carried out in three stages. The activities in these stages are (1) understanding the concept and modeling of journal writing activities, (2) implementing and getting into the habit of journal writing, and (3) authentic assessment by utilizing writing in student journals. The approach used in this research is qualitative, while the research design used is classroom action research. The classroom action research design was carried out in three research cycles. The research subjects were students of class VII G SMP Negeri 2 Palopo. The results showed that these activities could improve students' paragraph writing skills, both in quantity and quality of the paragraphs produced. Journal writing activities also make writing activities more interesting and meaningful for students. The increase is inseparable from the teacher's efforts to respond, develop dialogue, model how to write the correct paragraph, pay attention to mistakes that students often make, get used to it regularly, and provide various directions to awaken student's creativity in writing paragraphs. The teacher's guidance and direction are still given, even though journal writing is an informal writing activity. Based on the discussion of the research results, it is suggested that Indonesian language teachers should continue to apply journal writing habituation activities and be carried out with intensive and directed guidance. By looking at the contents of students' writing, it is also suggested to teachers of other subjects that this journal writing activity can be applied because in addition to practicing paragraph writing skills.